2013
DOI: 10.1055/s-0033-1333742
|View full text |Cite
|
Sign up to set email alerts
|

Krankheitskosten für Asthma und COPD bei Erwachsenen in der Bundesrepublik Deutschland

Abstract: The analysed cost-of-illness studies confirm that asthma and COPD are costly but results vary markedly. COPD due to its higher costs per case and its similar prevalence causes higher macroeconomic costs. Our results emphasise the economic relevance of prevention and disease management for these lung diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…A systematic review [18] of 7 COPD studies in Germany found annual costs per COPD patient between €1212 and €3492 (price year 2010) from a societal perspective. Most studies are limited to singular direct [4, 19, 20] or indirect [21] cost categories.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review [18] of 7 COPD studies in Germany found annual costs per COPD patient between €1212 and €3492 (price year 2010) from a societal perspective. Most studies are limited to singular direct [4, 19, 20] or indirect [21] cost categories.…”
Section: Discussionmentioning
confidence: 99%
“…Van Muijen and colleagues [ 78 ] reviewed only cohort studies of cancer-related work outcomes and were focused on English language. Steiner and colleagues [ 76 ] reviewed English publications published up until 2003, Breton and colleagues were focused only on diabetes and Krisch and colleagues focused on COPD in Germany [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review from Kirsch et al [ 16 ] estimated annual asthma-specific costs of €445 to €2,543 per patient from the social perspective. Cost data was collected from published cost-of-illness studies and adjusted for the year 2010.…”
Section: Discussionmentioning
confidence: 99%
“…The disease also represents a constant major economic burden for the German statutory healthcare system [ 2 , 10 , 11 ] with approximately €1.789 billion in 2008, accounting for 0.7 % of the total healthcare expenditure in Germany [ 12 ]. Several studies have assessed the costs of asthma in the German setting, considering a payer’s perspective or a societal perspective [ 2 , 5 , 10 , 11 , 13 16 ]. Yet, further research is required as data of the available studies is fragmentary and does not include all relevant cost domains.…”
Section: Introductionmentioning
confidence: 99%